New records of water mites (Acari, Hydrachnidia) from Iran with the description of one new species based on morphology and DNA barcodes - Pešić, Vladimir; Zawal, Andrzej; Saboori, Alireza; Smit, Harry (Zootaxa, 2021)
In this study, based on morphology and DNA barcodes, new records of water mites (Acari, Hydrachnidia) collected in August 2017 in North Iran are presented. Hydrodroma golestanica n. sp. (Hydrodromidae) is described as new for science. We also resurrect three previously synonymized species: Sperchon amuzgari Bader & Sepasgosarian, 1979 (Sperchontidae), Monatractides persicus Pešić & Saboori, 2004 and Torrenticola baueri Bader & Sepasgozarian, 1987 (Torrenticolidae).